2021
DOI: 10.1051/0004-6361/202141835
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas budget and characterization of intermediate-mass star-forming galaxies at z ≈ 2–3

Abstract: Star-forming galaxies (SFGs) with stellar masses below 1010 M⊙ make up the bulk of the galaxy population at z > 2. The properties of the cold gas in these galaxies can only be probed in very deep observations or by targeting strongly lensed galaxies. Here we report the results of a pilot survey using the Atacama Compact Array of molecular gas in the most strongly magnified galaxies selected as giant arcs in optical data. The selection in rest-frame ultraviolet (UV) wavelengths ensures that sources are regul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 142 publications
0
18
0
Order By: Relevance
“…Such a behavior has been interpreted as lensing magnification acting on a population with intrinsically steep number counts and detected above a constant CO flux threshold (Harris et al 2012). Note that our lens compilation, that includes lensed SFGs with low IR luminosities (Dessauges-Zavadsky et al 2015), at intermediate masses (Solimano et al 2021), and with extreme IR luminosities (Harrington et al 2018) produces a different distribution than the flat one reported in some previous works. An analysis of the L CO(1−0) -FWHM relation in lensed SFGs is beyond the scope of this work, but understanding the origin of such a flat trend might help to interpret our sample as well, and vice versa, even if our sources are not affected by lensing.…”
Section: Co Kinematicsmentioning
confidence: 54%
See 1 more Smart Citation
“…Such a behavior has been interpreted as lensing magnification acting on a population with intrinsically steep number counts and detected above a constant CO flux threshold (Harris et al 2012). Note that our lens compilation, that includes lensed SFGs with low IR luminosities (Dessauges-Zavadsky et al 2015), at intermediate masses (Solimano et al 2021), and with extreme IR luminosities (Harrington et al 2018) produces a different distribution than the flat one reported in some previous works. An analysis of the L CO(1−0) -FWHM relation in lensed SFGs is beyond the scope of this work, but understanding the origin of such a flat trend might help to interpret our sample as well, and vice versa, even if our sources are not affected by lensing.…”
Section: Co Kinematicsmentioning
confidence: 54%
“…detected SMGs by Bothwell et al (2013), the values measured in several cluster and protocluster members at 1.4<z<3.1 from the literature (see Table C.1), and those measured in lensed SFGs at 1.4<z<3.0 from the HATLAS, GEMS, SPT, and PCCS samples, and in intermediate mass or low L IR lensed SFGs (Harris et al 2012;Saintonge et al 2013;Dessauges-Zavadsky et al 2015;Cañameras et al 2015;Aravena et al 2016;Yang et al 2017;Harrington et al 2018;Solimano et al 2021). We also report the median values of each subsample 15 .…”
Section: Co Kinematicsmentioning
confidence: 97%
“…Such a behavior has been interpreted as lensing magnification acting on a population with intrinsically steep number counts and detected above a constant CO flux threshold (Harris et al 2012). It is relevant to point out that our lens compilation, which includes lensed SFGs with low IR luminosities (Dessauges-Zavadsky et al 2015), at intermediate masses (Solimano et al 2021), and with extreme IR luminosities (Harrington et al 2018) produces a different distribution than the flat one reported in some previous works. An analysis of the L CO(1−0) -FWHM relation in lensed SFGs is beyond the scope of this work, but understanding the origin of this flat trend might help to interpret our sample as well, and vice versa, even if our sources are not affected by lensing.…”
Section: Co Kinematicsmentioning
confidence: 64%
“…For each line, we report the measured width, whereas the luminosity is converted to the CO(1−0) luminosity using the line ratios from Bothwell et al (2013). We also show for comparison the relation between the CO(1−0) luminosity and FWHM derived for unlensed CO-detected SMGs by Bothwell et al (2013), the values measured in several cluster and protocluster members at 1.4 < z < 3.1 from the literature (see Table C.1), and those measured in lensed SFGs at 1.4 < z < 3.0 from the HAT-LAS, GEMS, SPT, and PCCS samples, and in intermediate mass or low L IR lensed SFGs (Harris et al 2012;Saintonge et al 2013;Dessauges-Zavadsky et al 2015;Cañameras et al 2015;Aravena et al 2016;Yang et al 2017;Harrington et al 2018;Solimano et al 2021). We also report the median values of each subsample 15 .…”
Section: Co Kinematicsmentioning
confidence: 87%
See 1 more Smart Citation